An expressional simplified mechanism in anthropomorphic face robot design. Issue 3 (9th July 2014) - Lin, Chyi-Yeu; Huang, Chun-Chia; Cheng, Li-Chieh
SUMMARY: The goal of this research is to develop a low-cost face robot which has a lower degree-of-freedom facial expression mechanism. Many designs of facial robots have been announced and published in the past. Face robots can be classified into two major types based on their respective degrees of freedom. The first type has various facial expressions with higher degrees of freedom, and the second has finite facial expressions with fewer degrees of freedom. Due to the high cost of the higher-degree-of-freedom face robot, most commercial face robot products are designed in the lower-degrees-of-freedom form with finite facial expressions. Therefore, a face robot with a simplified facial expression mechanism is proposed in this research. The main purpose of this research is to develop a device with a lower degree-of-freedom mechanism that is able to generate many facial expressions while keeping one basic mouth shape variation. Our research provides a new face robot example and development direction to reduce costs and conserve energy.